2021
DOI: 10.1080/24749508.2021.1923272
|View full text |Cite
|
Sign up to set email alerts
|

Land use/land cover changes and their impact on land surface temperature using remote sensing technique in district Khanewal, Punjab Pakistan

Abstract: The aim of this research was to assess the land use/land cover (LULC) changes and its impact on land surface temperature (LST) using remote-sensing (RS) technique in the district Khanewal, Punjab, Pakistan. Data were pre-processed using ERDAS imagine 15 and Arc GIS 10.4 software for layer stacking, mosaicking, and sub-setting of Landsat images. After pre-processing, the supervised classification scheme was applied for the years 1980, 2000, and 2020, which explains the maximum likelihood algorithm to identify L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(30 citation statements)
references
References 66 publications
2
26
0
2
Order By: Relevance
“…The areas around the city's central core with built-up areas and urban facilities have higher LST due to the impervious surfaces that expose such areas to greater solar radiation. The findings align with recent studies which have opined that the modification of land use due to various socio-economic factors has influenced local climatic condition in urban areas [6,73,78]. Additional studies are therefore needed in order to forecast and mitigate the environmental consequences of such changes.…”
Section: Implications Of Land-use Changes For Urban Climatesupporting
confidence: 86%
See 1 more Smart Citation
“…The areas around the city's central core with built-up areas and urban facilities have higher LST due to the impervious surfaces that expose such areas to greater solar radiation. The findings align with recent studies which have opined that the modification of land use due to various socio-economic factors has influenced local climatic condition in urban areas [6,73,78]. Additional studies are therefore needed in order to forecast and mitigate the environmental consequences of such changes.…”
Section: Implications Of Land-use Changes For Urban Climatesupporting
confidence: 86%
“…The study further witnessed an alteration of NDVI in 2020 with minimum and maximum values of −0.14 and +0.30, respectively. Previous studies indicate that areas with higher NDVI values signify forest and vegetated lands having agricultural farms, while lower NDVI values represent built-up areas and other land uses such as barren land and water bodies [61,73]. The NDVI maps showed a substantial decrease in vegetation cover, with lower NDVI values from 1991 to 2020.…”
Section: Normalised Difference Vegetation Indexmentioning
confidence: 86%
“…To achieve the optimal information from multispectral bands, we used multispectral Landsat imagery which contains more than three bands (for instance, Landsat imagery has 8 spectral bands: blue, green, red, NIR, SWIR1, thermal and SWIR2) Bhuiyan et al 2020a, b;Witharana et al 2019). Moreover, recent research showed that satellite-based remotely sensed Landsat images were successfully applied to generate LULC and LST maps to evaluate the land cover changes replacing natural vegetated surfaces with man-made infrastructures (Ibrahim 2017;Igun and Williams 2018;Hussain and Karuppannan 2021). Therefore, we conducted our study based on seven multi-spectral images acquired by the Landsat satellite sensor.…”
Section: Introductionmentioning
confidence: 99%
“…The STSS has been used to detect emerging clusters of shigellosis, measles, thyroid cancer and syndromic observation (Hohl et al 2020). Geographic information systems (GIS) has been applied to the field of agriculture in various domains including land management, regional agricultural resource information and planning (Hussain 2018;Majeed et al 2021), management of grain distribution and decisionmaking related to food production, research in the areas of agricultural production potential and crop yield estimation (Hussain et al 2020b;Khan et al 2020d;Rezaei et al 2020;Hussain and Karuppannan 2021). In the fight against COVID-19, GIS has played a significant role in different aspects, for example tracking of confirmed cases of COVID-19, rapid visualization of COVID data and combination of multi-source big data (Sun et al 2020;Zhou et al 2020;Zhang et al 2020).…”
Section: Introductionmentioning
confidence: 99%